2015
DOI: 10.4137/bci.s30377
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix and Integrins in Embryonic Stem Cell Differentiation

Abstract: Embryonic stem cells (ESCs) are pluripotent cells with great therapeutic potentials. The in vitro differentiation of ESC was designed by recapitulating embryogenesis. Significant progress has been made to improve the in vitro differentiation protocols by toning soluble maintenance factors. However, more robust methods for lineage-specific differentiation and maturation are still under development. Considering the complexity of in vivo embryogenesis environment, extracellular matrix (ECM) cues should be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 95 publications
0
26
0
Order By: Relevance
“…Integrins are a large family of heterodimeric cell-surface adhesion receptors which mediate cell-matrix and cell-cell interactions (Gasparski & Beningo, 2015;Wang, Luo, & Leighton, 2015). They are generally composed of noncovalently linked α and β subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are a large family of heterodimeric cell-surface adhesion receptors which mediate cell-matrix and cell-cell interactions (Gasparski & Beningo, 2015;Wang, Luo, & Leighton, 2015). They are generally composed of noncovalently linked α and β subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized microenvironments (niches) are suggested to provide the multiple extracellular signals necessary to maintain the stemness of hPSCs 7 10 . Previous studies have indicated that niche-dependent extracellular matrices (ECMs) facilitate the self-renewal and pluripotency of PSCs 11 , 12 , with growth factors (such as basic fibroblast growth factor, bFGF, and epidermal growth factor, EGF) regulating their growth and survival 13 . Recent studies also suggest that niche-providing cytokines are possibly involved in the maintenance of PSCs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, integrins have also been demonstrated to play a role in stem cell differentiation. 46 The Notch signaling pathway has been shown to promote vascular maturation, 47 even by inducing integrin-mediated cell adhesion to the endothelial basement membrane. 48 We further tested the effect of LXW7 on the expression of immature and mature endothelial markers and Notch signaling pathway genes.…”
Section: Resultsmentioning
confidence: 99%